Multiscale boundary conditions for non-Fickian diffusion applied to drug-eluting stents - Gudiño, Elías; Oishi, Cassio M. [UNESP]; Sequeira, Adélia (Society for Industrial & Applied Mathematics (SIAM), 2017)
We propose a multiscale model for the study of blood flow, plasma filtration, and non-Fickian mass transport by a coronary drug-eluting stent. We derive an analytic solution of a one-dimensional model for non-Fickian diffusion and replace the problem of drug transport in the coating of the stent with suitable boundary conditions. In this way, the computational cost of numerical simulations in realistic three-dimensional stent geometries is reduced. Numerical experiments to show the effectiveness of the method are also presented.
Keywords: Drug delivery; Drug-eluting stents; Multiscale models; Non-Fickian diffusion